Philosophy of State: Social Action and State Power according to Max Weber - Nur Rohim Yunus (ADALAH, 2019)
Max Weber was a sociologist known for his theoretical approach to "Social Action". Max Weber's methodology differed from structural theorists such as Émile Durkheim and Karl Marx in that he used this form of social action analysis. In his view, social action is the recognition that individual action is directed by certain motives and goals. An action has a subjectivity of meaning and can affect other people, so that it has a subjectivity of meaning for both oneself and others. Power, in contrast, is defined as the ability to carry out the will of someone who opposes it in a social setting, regardless of the source of that ability.